'Gotta Go Visit Family': Reconsidering the Relationship Between Tourism and Transnationalism. Issue 7 (2nd March 2015) - von Koppenfels, Amanda Klekowski; Mulholland, Jon; Ryan, Louise
Abstract: A comparative examination of two groups of highly skilled Global North migrants – US citizens (Americans) in London, Berlin, and Paris and French citizens in London – this paper explores the nature of these migrants' visits home, situating these visits between tourism and transnationalism. We question whether there has been a tendency to conceptualise visits home by migrants from the Global North as tourism and those from the Global South as transnational engagement. We found that our study participants' visits home often incorporated visits to family, relaxation, tourism, and cultural transmission to children, suggesting there is not a clear distinction between tourism and transnationalism. At the same time, we noted a certain tension between transnationalism, here primarily familial obligations, and tourism, as migrants sought to balance a felt need to visit family and a desire to have some aspect of relaxation or tourism. Visits home also often necessitated negotiations of social relations – often in both home and host countries. Finally, we noted a bidirectionality in visits: migrants visited home, but family and friends visited them as well, which also serves to maintain social connections with home, suggesting that the implications of this bidirectionality for the nature of transnationalism are an area for future research. Copyright © 2015 John Wiley & Sons, Ltd.